Penerapan Teknologi Komunikasi Bisnis dalam Meningkatkan Efisiensi Bisnis - Suwandi Suwandi; Manda Putra Hutabarat; Muhammad Rangga aldjudin; Lany Melania (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
In the growing era of Artificial Intelligence (AI), communication technology plays an important role in supporting the effectiveness and efficiency of business operations. This research aims to analyze how the implementation of business communication technologies, such as email, video conferencing, online collaboration platforms, and information management systems, can improve efficiency in work processes and decision making. The methods used in this research are literature study and case analysis of several companies that have successfully integrated communication technology in their business activities. The results show that the strategic use of communication technology can speed up the flow of information, reduce operational costs, and improve productivity and coordination between teams. The findings emphasize the importance of appropriate adoption of communication technology in improving business competitiveness amidst changing market dynamics.